أنساق التفكير الإبداعي في كتابات الأستاذ محمد أحمد الراشد - Badi, Jamal Ahmed Bashier (International Islamic University Malaysia Press, 2015)
Despite their large number, there is hardly a single book among Mohammed Ahmed al-Rashid’s works that does not touch on thinking in general or creative thinking in particular since he became known as a writer more than three decades ago. Over the recent years a new series comprising more than twenty treatises by him has been published in which al-Rashid’s has announced the birth of a new art in the field of creative thinking by the name “Dynamic Movement”. It is an art with its principles grounded in the sources of Islamic thought and which is inspired by its values and worldview, but that also draws upon modern disciplines. This study examines al-Rashid’s writings in order to uncover the most important patterns of creative thinking in his work and identify some of the aesthetic and artistic aspects characterizing his thought and by which he endeavours to impress his readers’ minds. All this aims to bring into perspective the most important principles of creativity and the mechanisms governing it in the context of this writer’s new art.